Environmental education outcomes for conservation: A systematic review - Ardoin, Nicole M.; Bowers, Alison W.; Gaillard, Estelle (Biological Conservation, 2020)
Effective environmental education represents more than a unidirectional transfer of information: rather, this suite of tools develops and enhances environmental attitudes, values, and knowledge, as well as builds skills that prepare individuals and communities to collaboratively undertake positive environmental action. Environmental education also facilitates connections between actionable research findings and on-the-ground practices, creating synergistic spaces where stakeholders collaborate to address dynamic environmental issues over time. Because of this commitment to application and iteration, environmental education can result in direct benefits to the environment and address conservation issues concretely. Yet, the path to achieving those tangible impacts can be winding, with robust data documenting changes challenging to produce. To better understand the research-implementation spaces where those environmental education outcomes occur, are measured, and are reported, we undertook a systematic review of research on environmental education's contributions to conservation and environmental quality outcomes. Given the variation in research designs and data, we used a mixed-methods approach to the review; analysis of the 105 resulting studies documented strongly positive environmental education outcomes overall and highlighted productive research-implementation spaces. Chi-square analyses revealed that programs reporting direct outcomes, compared with those reporting indirect outcomes, differed on primary topic addressed. A narrative analysis indicated that environmental education programs documenting direct impacts included: a focus on localized issues or locally relevant dimensions of broader issues; collaboration with scientists, resource managers, and/or community organizations; integrated action elements; and intentional measurement/reporting structures. Those themes suggest program development and documentation ideas as well as further opportunities for productive research-implementation spaces.
Keywords: Conservation social sciences; Environmental education; Environmental management; Public engagement; Research-implementation spaces; Systematic review